2Long-read sequencing revealed alterations of microbial relationship between tongue coating and gastric mucosa in patients with gastric intestinal metaplasia - Wu Jianping; Li Meifeng; Hua Zhaolai; Lu Bin; Xiang Jiao; Wu Zhenfeng; Zhang Junfeng (KeAi Communications Co., Ltd., 2023)
Objective: To explore the microbial correlation between oral tongue coating (TC) and gastric mucosa (GM) in patients with gastric intestinal metaplasia (GIM). Methods: The present study recruited 1360 volunteers for upper gastrointestinal cancer screening. The microbiota in TC and GM were profiled by long-read sequencing of full-length 16S rRNA gene. The microbial diversity, community structure, and linear discriminant analysis effect size (LEfSe) were analyzed by the software Visual Genomics. SparCC correlation analysis was used to construct the commensal network and the graphical display was conducted by R software. Results: The population included 44 patients with precancerous GIM, and 28 matched controls with negative rapid urease test (RUT) and non-symptomatic chronic superficial gastritis (CSG). No significant difference in diversity was observed between GIM patients and controls in TC or GM microbiota (P > 0.05). Patients had a higher percentage of 41 - 60 co-occurring operational taxonomic units (OTUs) between TC and GM than controls (34.1 % vs. 25.0 %) (P < 0.05). The LEfSe showed that TC Prevotella melaninogenica and three gastric Helicobacter species (i.e., Helicobacter pylori, Helicobacter pylori XZ274, and Helicobacter pylori 83) were enriched in patients with GIM. Furthermore, GIM patients with positive RUT had a lower percentage of co-occurring OTUs over 20 (P < 0.05), and lower abundances of gastric Veillonella, Pseudonocardia, and Mesorhizobium than those with negative RUT (P < 0.05). The commensal network between TC and GM was more complex in GIM patients than in controls. GIM patients with positive RUT demonstrated more bacterial correlations between TC and GM than those with negative RUT. Finally, the serum ratio of PG-I/II was negatively correlated with three gastric Helicobacter species (Helicobacter pylori, Helicobacter pylori XZ274, and Helicobacter pylori 83) in patients with negative RUT (P < 0.05), and negatively correlated with two TC species (Fusobacterium nucleatum subsp. nucleatum and Campylobacter showae) in patients with positive RUT (P < 0.05). Conclusion: The development of GIM potentiated the commensal network between oral TC and GM, providing microbial evidence of the correlation between TC and the stomach.